Reformation Resources for Contemporary Eco‐Justice Theology. Issue 2 (8th June 2016) - Saler, Robert C.; Nelson, Derek R.
Abstract: Reformation theology has two significant contributions to make to a renewal of environmental theology. Its heritage of sin exposes the fact that human efforts at intervention in the environment are only ambiguously good and in need of redemption themselves. Its heritage of freedom exposes some efforts toward environmental healing as works‐righteousness, available to be transformed by God in hope for a heavenly and earthly future.